Health-care organization for the management and surveillance of SARS-CoV-2 infection in children during pandemic in Campania region, Italy - Francesco Nunziata; Eugenia Bruzzese; Marco Poeta; Luca Pierri; Andrea Catzola; Gian Paolo Ciccarelli; Edoardo Vassallo; Emma Montella; Andrea Lo Vecchio; Alfredo Guarino (BMC, 2020)
Abstract Background In comparison with adults, severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection in children has a milder course. The management of children with suspected or confirmed coronavirus disease (COVID-19) needs to be appropriately targeted. Methods We designed a hub-and-spoke system to provide healthcare indications based on the use of telemedicine and stringent admission criteria, coordinate local stakeholders and disseminate information. Result Between March 24th and September 24th 2020, the Hub Centre managed a total of 208 children (52% males, median age, 5.2, IQR 2-9.6 years) with suspected or confirmed COVID-19. Among them, 174 were managed in cooperation with family pediatricians and 34 with hospital-based physicians. One hundred-four (50%) received a final diagnosis of SARS-CoV-2 infection. Application of stringent criteria for hospital admission based on clinical conditions, risk factors and respect of biocontainment measures, allowed to manage the majority of cases (74, 71.1%) through telemedicine. Thirty children (28%) were hospitalized (median length 10 days, IQR 5-19 days), mainly due to the presence of persistent fever, mild respiratory distress or co-infection occurring in infant or children with underlying conditions. However, the reasons for admission slightly changed over time. Conclusion An hub-and-spoke system is effective in coordinate territorial health-care structures involved in management paediatric COVID-19 cases through telemedicine and the definition of stringent hospital admission criteria. The management of children with COVID-19 should be based on clinical conditions, assessed on a case-by-case critical evaluation, as well as on isolation measures, but may vary according to local epidemiological changes.